Enhanced interfacial, electrical, and flexural properties of polyphenylene sulfide composites filled with carbon fibers modified by electrophoretic surface deposition of multi-walled carbon nanotubes. (June 2018) - Park, Min; Park, Jong Hyuk; Yang, B.J.; Cho, Jaehyun; Kim, Seong Yun; Jung, Inhwa
Abstract: Electrophoresis can be an effective approach for depositing carbon nanotubes (CNTs) on the surface of carbon fiber (CF). Nevertheless, it has been rarely reported on polyphenylene sulfide (PPS) composites filled with CFs surface-modified by CNTs based on electrophoresis. In this study, we investigated the electrophoresis process conditions that can completely coat CF with multi-walled CNTs (MWCNTs) using self-manufactured electrophoresis equipment, and the enhancement of interfacial, electrical and flexural properties of PPS composites by introducing CFs coated with MWCNTs based on electrophoresis. In particular, interfacial shear strength (IFSS) of the PPS composites was measured by microbond tests and improved by about 41.7% due to the MWCNTs introduced on the surface of CFs. These enhancements were theoretically explained by an interface-modified CF-based micromechanical model. Introducing MWCNTs on the CF surface based on electrophoresis was demonstrated to be an effective method for improving the interfacial, electrical and flexural properties of PPS composites.